2016
DOI: 10.1186/s12934-016-0458-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of Synechocystis PCC6803 for the photoautotrophic production of the sweetener erythritol

Abstract: BackgroundErythritol is a polyol that is used in the food and beverage industry. Due to its non-caloric and non-cariogenic properties, the popularity of this sweetener is increasing. Large scale production of erythritol is currently based on conversion of glucose by selected fungi. In this study, we describe a biotechnological process to produce erythritol from light and CO2, using engineered Synechocystis sp. PCC6803.MethodsBy functionally expressing codon-optimized genes encoding the erythrose-4-phosphate ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…Recently, Janek et al [ 15 ] identified an ylER enzyme ( YALI0F18590p ) in Y. lipolytica based on sequence similarity with erythrose reductase from Candida magnoliae [ 7 ]. These ER enzymes, belonging to the aldose reductase family (ALR), have also been reported mainly dependent on NADPH as a redox co-factor [ 5 , 18 , 21 , 22 ]. Different ER isozymes have been reported in T. megachiliensis [ 18 ] and Moniliella sp.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Janek et al [ 15 ] identified an ylER enzyme ( YALI0F18590p ) in Y. lipolytica based on sequence similarity with erythrose reductase from Candida magnoliae [ 7 ]. These ER enzymes, belonging to the aldose reductase family (ALR), have also been reported mainly dependent on NADPH as a redox co-factor [ 5 , 18 , 21 , 22 ]. Different ER isozymes have been reported in T. megachiliensis [ 18 ] and Moniliella sp.…”
Section: Resultsmentioning
confidence: 99%
“…van der Woude et al. aimed to improve erythritol yield by overexpressing phosphoketolase or TK gene and consequently increase erythrose‐4‐P availability in the metabolic pathway of erythritol in Synechocystis PCC6803, while minimal effects were observed. Bellou et al.…”
Section: Resultsmentioning
confidence: 99%
“…According to the study of Ghezelbash et al [35], no remarkable difference was observed in ER gene expression levels between the wild-type Y. lipolytica and mutant strains, and the specific activity of ER was probably due to the modification of the active center of the enzyme. van der Woude et al [36] aimed to improve erythritol yield by overexpressing phosphoketolase or TK gene and consequently increase erythrose-4-P availability in the metabolic pathway of erythritol in Synechocystis PCC6803, while minimal effects were observed. Bellou et al [37] reported that the activities of the key enzymes involved in lipid synthesis by Y. lipolytica were influenced at post-transcriptional level rather than mRNA expression level when cultivated under nitrogen-and magnesium-limited conditions.…”
Section: Expression Levels Of Relative Enzymes In M53mentioning
confidence: 99%
“…The expressed enzymes can then convert erythrose-4-phosphate into erythritol. Erythrose-4-phosphate is inherent and is built as a key intermediate of the CO 2 -fixing Calvin Benson Bassham cycle (van der Woude et al 2016 ).…”
Section: Production—history and Developmentmentioning
confidence: 99%